The global rules of art : the emergence and divisions of a cultural world economy - Buchholz, Larissa (Princeton : Princeton University Press, 2022)
A trailblazing look at the historical emergence of a global field in contemporary art and the diverse ways artists become valued worldwidePrior to the 1980s, the postwar canon of "international" contemporary art was made up almost exclusively of artists from North America and Western Europe, while cultural agents from other parts of the world often found themselves on the margins. The Global Rules of Art examines how this discriminatory situation has changed in recent decades. Drawing from abundant sources--including objective indicators from more than one hundred countries, multiple institutional histories and discourses, extensive fieldwork, and interviews with artists, critics, curators, gallerists, and auction house agents--Larissa Buchholz examines the emergence of a world-spanning art field whose logics have increasingly become defined in global terms.Deftly blending comprehensive historical analyses with illuminating case studies, The Global Rules of Art breaks new ground in its exploration of valuation and how cultural hierarchies take shape in a global context. The book's innovative global field approach will appeal to scholars in the sociology of art, cultural and economic sociology, interdisciplinary global studies, and anyone interested in the dynamics of global art and culture.
Frontmatter -- Contents -- List of Illustrations -- List of Tables -- Preface: An Unsettling Success -- 1 A Global Field Approach to Art and Culture -- Part I. The Emergence of a Global Field in the Contemporary Visual Arts -- 2 The Genesis of a Global Artistic Subfield -- 3 From an International Avant-Garde Market to a Global Commercial Subfield -- Part II. Dynamics of Artistic Recognition in the Globalizing Field -- 4 Cross-Border Valuation between Art Experts and the Market -- 5 Diversity and Careers in a Dual Cultural World Economy -- Part III. Creative Lives -- 6 Becoming a Global Artist at the Relatively Autonomous Pole -- 7 The Hype of the Chinese Market Star Yue Minjun -- 8 "Global Art" between Autonomy and Heteronomy -- Epilogue -- Acknowledgments -- Appendices -- Notes -- References -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 20, 2022).
JSTOR
Keywords: Art -- Marketing; Art, Modern -- 20th century -- Economic aspects; Art, Modern -- 21st century -- Economic aspects; Art and globalization; Art -- Commercialisation; Art -- 20e siècle -- Aspect économique.; Art -- 21e siècle -- Aspect économique.; Art et mondialisation; art market; ART / Business Aspects; Art and globalization; Art -- Marketing; Art, Modern -- Economic aspects; The arts: general issues; Art and Design; 1900-2099; Andy Warhol; Art Basel; Art Express; Art Journal (College Art Association journal).; Art auction; Art critic; Art criticism; Art department; Art for art's sake; Art group; Art history; Art methodology; Art movement; Artforum; Artnet; Artprice; Auction; Capital control; Career; Central bank; Commercial art; Competition (economics).; Competitive landscape; Contemporary art; Core business; Cultural Revolution; Cultural capital; Cultural imperialism; Curator; Currency; Deterritorialization; Documenta; Economic capital; Economic globalization; Ethnoscape; Externality; Fluxus; General Agreement on Tariffs and Trade; Geopolitics; Global Exchange; Global Finance (magazine).; Global Leadership; Global Map; Global administrative law